Towards an understanding of mental representation - E. A. Lukjanchenko (Vestnik MGIMO-Universiteta)
The article deals with traditional ways of understanding human cognitive processes in terms of key ideas of philosophical, cultural, and linguistic sciences, as well as modern ideas concerning the nature of mental representation.